Implementasi Kode Etik Jurnalisitik Wartawan di Pemerintah Provinsi Sumatera Selatan - Aldino, Mohammad; Sakir, Icuk Muhammad; Hestirinaih, Deby Chintia (@-Publik: Jurnal Administrasi Publik, 2023)
The enactment of Law Number 40 of 1999 concerning the Press and Law Number 32 of 2000 concerning Broadcasting has ushered the mass media business into a new paradigm, where freedom of speech, expression of thoughts, and opinions are implicated with the emergence of various local and national media, whether in print or electronic form. The quality, whether good or bad, of the content in mass media largely depends on the sharpness of journalists in seeking and selecting their news materials. In order to maintain professionalism, it is imperative for journalists to always use the correct methods and procedures in collecting, processing, and disseminating information while adhering firmly to professional ethics. The limited competence and quality of human resources of journalists covering the Provincial Government of South Sumatra have resulted in suboptimal journalistic activities, indicating a lack of knowledge and responsibility in accordance with the professionalism required. From this background, the author is interested in conducting research in the form of a thesis with the title: "Implementation of Journalistic Code of Ethics by Journalists in the South Sumatra Provincial Government." The purpose of this research is to analyze the implementation of the Journalistic Code of Ethics by journalists in the South Sumatra Provincial Government. The research method used by the researcher is a qualitative approach. Based on the research results, it is revealed that the Indonesian Journalists Association implements the Journalistic Code of Ethics by journalists in the South Sumatra Provincial Government based on four important aspects of implementation: a) Continuous Communication Process, b) Resources, c) Disposition/Attitude of Implementers, d) Bureaucratic Structure. It can be concluded that overall, the implementation of the Journalistic Code of Ethics by journalists in the South Sumatra Provincial Government has been carried out effectively.